Inverter Design Inverter Full - Bridge 1 Phase with DSP F28069M Using SPWM Technique - Putri, Ratna Ika; Maulana, Fahrul; Haryadi, Herman (Majalah Ilmiah Teknologi Elektro; Vol 20 No 2 (2021): (Juli-Desember) Majalah Ilmiah Teknologi ElektroDO - 10.24843/MITE.2021.v20i02.P09, 2021)
Abstract- Along with the development of technology, with the inverter you can get temporary electrical energy for several electronic devices using a DC source. In this paper, the designed inverter is a type of 1-phase inverter with an output voltage greater than the input voltage. The inverter uses the SPWM (sinusoidal pulse width modulation) technique, as a switching process. The purpose of this research is to design a single phase full-bridge inverter by adjusting the switching mosfet using DSPF28069M to produce a sinusoidal wave output. A single phase full-bridge inverter is designed by changing the voltage from the battery or power supply from 12-24 VDC to 12-24 VAC. Then the voltage 12-24 VAC is increased by using a step up transformer. The inverter test results of 17 VDC using a 15/220 VAC step up transformer with an efficiency of 81.4%. The results of the SPWM signal with the inverter input 17 VDC, the voltage issued by the inverter is 227 VAC without load, 194 VAC with a load power of 22 Watts, amounting to 178 VAC with a load power of 40 Watts, amounting to 162 VAC with a load power of 88 Watts, and amounting to 154 VAC with a load power of 128 Watts.